PENGUJIAN TRICHODERMA SP. SEBAGAI PENGENDALI HAWAR DAUN BIBIT KAKAO YANG DISEBABKAN OLEH PHYTHOPTHORA PALMIVORA - ., Sutarman (Universitas Lampung, 2017)
Analysist for Trichoderma sp. as the controller of the cocoa seedlings leaf blight which caused by Phythopthora palmivora. This study aims to determine: survival and ability to live of Trichoderma sp. isolates TCN-Klp supported by predisposing wounding or without wounding the leaves as well as the ability to suppress P. palmivora inoculated on the leaves of cocoa seedlings with and without wounding the leaves before inoculation. The research conducted at the Microbiology Laboratory and Greenhouse of Agriculture Faculty, Universitas Muhammadiyah Sidoarjo on March-July 2015. There were two kinds of experiments: inoculation without wounding the leaves (1st experiment) and inoculation with wounding leaves (2nd experiment). Both of them were done by inoculation treatment: pathogens, Trichoderma, pathogens and Trichoderma simultaneously, then pathogens and incubated for 2x24 hours then inoculated. Both kinds of experiments were arranged in a complete randomize design (CRD) with 3 times of replication for 1st experiment and 4 times of replication for 2nd experiment. The data of result was analyzed by ANOVA followed by 5% test level of Duncan test. The results showed that the isolates TCN-Klp of Trichoderma sp: (i) had own survival and ability to live well in the leaf surface without injury, and (ii) was able to suppress pathogens by inoculation simultaneously, which was preceded and precede the pathogens with a gap of 24 hours on with and without wounding leaves at 10 days after inoculation.